PENGARUH SEDIAAN GEL EKSTRAK BUAH TOMAT (Lycopersicum esculentum Mill) TERHADAP WAKTU PENYEMBUHAN LUKA PADA TIKUS GALUR WISTAR SEBAGAI HEWAN MODEL DIABETES MELITUS - Ayu Indah Carolina (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Diabetes mellitus is a chronic disease that is characterized by blood glucose levels exceed to normal range and cause various complications; one is ulcer/diabetic wound. Chronic wounds in patients with diabetes mellitus are caused by oxidative stress due to the increased production of free radicals. One of the free radicals are ROS (Reactive Oxygen Species) that will increase which causes prolonged inflammatory phase of wound healing then the time of wound healing will also be elongated. It needs fairly powerful antioxidants; one of them is a carotene lycopene which gives the red color in tomatoes. Therefore, we need a research to determine the effect of tomatoes towards the time of wound healing that are tested in the preparation of gel. The preparation of gel can retain moisture as it supports wound epithelization. True experimental study with randomized design (simple randomized designed) was conducted in the Laboratory of Pharmacology Faculty of Medicine, Udayana University. The result shows there is significant effect of gel preparation of tomato fruit extracts towards the time of wound healing with the results of One-Way ANOVA test showed p = 0.000 (p < 0.05) which means that H0 is rejected. The time of wound healing with treatment of gel with tomato extract is the shortest time of wound healing between the animal model of diabetes mellitus that is an average of 12.17 days (with placebo gel on average of 13.83 days, with a wet gauze bandage NaCl 0.9% on average of 20.00 days) and the group that was not induced by alloxan recovered an average of 8.00 days. For further research, this study is expected to proceed to a higher level so that the gel preparation of tomato fruit extract can be used as an alternative natural-based modern wound care in the management of diabetic wounds.